Tifinagh Characters Recognition Using Simple Geometric Shapes - M. Boutaounte; Y. Ouadid (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In this paper we present method of features extraction based on decomposition of the characters into several simple geometric shapes (segment, arc) by detecting the branch points and end points, as it explained follow a new methods are using to treated the obtained information in order to decide if the characters need to add more key points also in this step we extracte the type of the shapes (segment or arc) and the orientation. The next step of characters recognition different methods are used such as neural network (NN), K-mean and support vector machine (SVM) classifier. The results shown in this paper are obtained using the IRCAM database.